Proteins associated with cork formation in Quercus suber L. stem tissues. (Journal of proteomics, 2011)
Cork (phellem) formation in Quercus suber stem was studied by proteomic analysis of young shoots of increasing age (Y0, Y1 and Y4) and recently-formed phellem (Y8Ph) and xylem (Y8X) from an 8-year-old branch. In this study 99 proteins were identified, 45 excised from Y8X and 54 from Y8Ph. These ones, specifically associated with phellem, are of "carbohydrate metabolism" (28%), "defence" (22%), "protein folding, stability and degradation" (19%), "regulation/signalling" (11%), "secondary metabolism" (9%), "energy metabolism" (6%), and "membrane transport" (2%). The identification in phellem of galactosidases, xylosidases, apiose/xylose synthase, laccases and diphenol oxidases suggests intense cell wall reorganization, possibly with participation of hemicellulose/pectin biosynthesis and phenol oxidation. The identification of proteasome subunits, heat shock proteins, cyclophylin, subtilisin-like proteases, 14-3-3 proteins, Rab2 protein and enzymes interacting with nucleosides/nucleic acids gives additional evidence for cellular reorganization, involving cellular secretion, protein turnover regulation and active control processes. The high involvement in phellem of defence proteins (thioredoxin-dependent peroxidase, glutathione-S-transferase, SGT1 protein, cystatin, and chitinases) suggests a strong need for cell protection from the intense stressful events occurring in active phellem, namely, desiccation, pests/disease protection, detoxification and cell death. Identically, highly enhanced defence functions were previously reported for potato periderm formation.